Efficiency of probiotic culture consortium application for disinfection of dairy farm premises and prevention of mastitis in cows (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: In this work, the effect of probiotics on the state of the microbial background of the livestock building, on the state of udder teats, and on the prevalence of latent mastitis was investigated. Long-term use of the consortium has bactericidal activity against all cultures studied, especially the causative agent of mastitis, Staphylococcus aureus, except Proteus mirabilis, Proteus vulgaris, and Escherichia coli. Materials and Methods: The washes from animal housings and milk samples were collected from the dairy farms “Astana-Onim” Joint Stock Company and “Rodina” Limited Liability Partnership (Kazakhstan). The cleaning solutions and probiotic agents were applied directly to the udder teats of cows before and after milking. Diagnosis of subclinical mastitis was performed using the Kenotest rapid mastitis test. Directly counting the number of somatic cells in the collected milk samples from each cow was performed on a somatic cell counter. Results: Pathogenic microorganisms, including S. aureus bacteria (50% of samples) and bacteria of the E. coli group, Enterobacter aerogenes, and P. mirabilis (36% of samples), were detected on the udder skin and milk wipes. Using a consortium of probiotic microorganisms positively affects the mammary gland more quickly than using mastitis prevention agents alone. Probiotic use for a month resulted in a significant improvement in udder teat condition, with 60.7% of teats showing normal physiological reaction to milking, a decrease in complicated hyperkeratosis, and an increase in uncomplicated mastitis. The studies showed that in the experimental group, there was a 1.5-fold reduction in the number of cows with clinically pronounced mastitis. The experimental group showed no significant changes in the number of animals with high somatic cell levels before and after the study, while the control group without probiotics had a significant increase in diseased animals after 1 month. Conclusion: The use of a probiotic consortium has shown promising results in reducing the incidence of mastitis and improving milk quality in cows.  J. Adv. Vet. Anim. Res., 10(2): 185–195, June 2023http://doi.org/10.5455/javar.2023.j668